2013
DOI: 10.1002/hed.23301
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral vessel density as prognostic factors in head and neck squamous cell carcinoma: A meta‐analysis of literature

Abstract: High counts of LVD, not MVD, are associated with worse 5-year overall survival (OS) in patients with HNSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 54 publications
1
25
0
Order By: Relevance
“…They demonstrated a correlation between tumor size and the higher MVD/CD105 ratio in oral cancers [14]. Based on this and similar studies, the concept emerged that the high MVD/CD105 values are associated with the presence of lymph node metastasis and poorer 5-year survival [1519]. This and other studies [20] suggested that CD105 expression might serve as an important prognostic factor in HNSCC, enabling the identification of patients at high risk of recurrence and shorter survival.…”
Section: Discussionmentioning
confidence: 97%
“…They demonstrated a correlation between tumor size and the higher MVD/CD105 ratio in oral cancers [14]. Based on this and similar studies, the concept emerged that the high MVD/CD105 values are associated with the presence of lymph node metastasis and poorer 5-year survival [1519]. This and other studies [20] suggested that CD105 expression might serve as an important prognostic factor in HNSCC, enabling the identification of patients at high risk of recurrence and shorter survival.…”
Section: Discussionmentioning
confidence: 97%
“…S4B] and are thus considered relevant to the disease. Lymph-angiogenesis is significant clinically for many types of cancers but most appealing in head and neck cancer because lymph node metastasis is the most important clinical parameter for this malignancy (33). We found reduced lymph vessel density in Hpa2 tumors combining with a comparable decrease in VEGF-C expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, lymphatic vessel density (LVD) is expected to be an important factor, which determinates patients' survival (23). In spite of the discrepancies in the results of studies on the prognostic significance of LVD in breast cancer patients (9,10), the current meta-analyses demonstrated that, this parameter could be of prognostic significance in patients with breast (24), colorectal (25), head and neck cancers (26) as well as in melanoma (27). However, the authors of the aforementioned studies stress that the standardization of the LVD assessment and the future confirmatory studies on its prognostic/predictive role, are necessary.…”
Section: Introductionmentioning
confidence: 63%